A movie of the accretion disk of dwarf nova Ex Draconis - Giannakis, O.; Harlaftis, E. T.; Papadimitriou, C.; Niarchos, P. G.; Gazeas, K.; Manimanis, V.; Steeghs, D.; Boffin, H. (The Astrophysics of Cataclysmic Variables and Related Objects, 2005)
The outburst and eclipse characteristics of the eclipsing dwarf nova EX Dra prompted us to monitor it during the months July-August 2000 with the 1.2m telescope of the National Observatory of Athens (NOA). Here, we present an eclipse mapping study of the July 2000 light curves. B-band of the August 2000 data have been presented by Harlaftis et al. (2002).